A remotely driven and controlled micro-gripper fabricated from light-induced deformation smart material. (8th August 2016) - Huang, Chaolei; Lv, Jiu-an; Tian, Xiaojun; Wang, Yuechao; Liu, Jie; Yu, Yanlei
Abstract: Micro-gripper is an important tool to manipulate and assemble micro-scale objects. Generally, as micro-gripper is too small to be directly driven by general motors, it always needs special driving devices and suitable structure design. In this paper, two-finger micro-grippers are designed and fabricated, which utilize light-induced deformation smart material to make one of the two fingers. As the smart material is directly driven and controlled by remote lights instead of lines and motors, this light-driven mode simplifies the design of the two-finger micro-gripper and avoids special drivers and complex mechanical structure. In addition, a micro-manipulation experiment system is set up which is based on the light-driven micro-gripper. Experimental results show that this remotely light-driven micro-gripper has ability to manipulate and assemble micro-scale objects both in air and water. Furthermore, two micro-grippers can also work together for cooperation which can further enhance the assembly ability. On the other hand, this kind of remotely controllable micro-gripper that does not require on-board energy storage, can be used in mobile micro-robot as a manipulation hand.